THE INFLUENCE OF AFFECTIVE COMMITMENT, PERSON JOB FIT AND POSITIVE AFFECTIVY ON KNOWLEDGE SHARING IN BMT BINA IHSANUL FIKRI EMPLOYEES YOGYAKARTA CITY - Susilo Dwi Pujiyanto; Abdul Choliq Hidayat; Ema Nurmaya (Jurnal Ekonomi, 2023)
This study aims to determine the partial and simultaneous effect of Affective Commitment, Person Job-fit and Positive Affectivity on Knowledge Sharing of BMT Bina Ihsanul Fikri Yogyakarta employees. In this study there are 4 hypotheses, namely, H1: Affective Commitment has a positive and significant effect on Knowledge Sharing, H2: Person Job-fit has a positive and significant effect on Knowledge Sharing, H3: Positive Affectivity has a positive and significant effect on Knowledge Sharing, H4: Affective Commitment , Person Job-fit and Positive Affectivity simultaneously influence Knowledge Sharing. This hypothesis was tested using a sample of 85 respondents from BMT Bina Ihsanul Fikri Yogyakarta employees. The data analysis technique used is multiple linear regression with the SPSS 25 application. The results of this study indicate that the independent variables simultaneously influence the dependent variable. This is indicated by the R2 value of 19.7%. This research can provide theoretical and practical benefits.